Glaucoma and dietary intake: a scoping review - Edokpa, Genesis Daniel; McFarlane, Shelly Rose-Marie (Frontiers in Nutrition, 2024)
Studies have suggested that dietary intake may influence the incidence and progression of open-angle glaucoma. However, dietary modification is not usually included in the clinical management of glaucoma. The aim of this scoping review was therefore to map the evidence and determine the nature and extent of research done on "diet and glaucoma" and identify any gaps in this area of scholarship. Materials and methods: A comprehensive search of academic literature was conducted from two relevant electronic databases: PubMed and ScienceDirect. Primary studies that explored the relationship between dietary intake and glaucoma were included if the principal exposure was "diet" and if dietary habits were assessed with dietary questionnaires. The glaucoma outcomes of interest were visual field, retinal nerve fibre layer and/or optic nerve head features. Results: Nineteen (19) studies were included in the final qualitative synthesis. The dates of publication ranged from 2003 -2023. About eighty percent of the studies found some significant associations between glaucoma and dietary intake. However, most studies (95%) were observational, i.e., 7 (37 %) used a cross-sectional design, 10 (53%) used a prospective cohort design; and 1 (or 5%) used a nested case-control study design. Only 1 study (or 5%) used a randomized intervention trial. Furthermore, while all studies investigated dietary intake with questionnaires, only 2 studies (or 11%) went further to include assessment of nutritional biomarkers. Conclusion: Although miscellaneous evidence supports the concept that diet may play a role in glaucoma, most data are unfortunately observational without proven causality, reporting associations from subjective dietary questionnaires. More well-designed studies are required, especially randomized controlled trials that can prove causality.